2022
DOI: 10.1111/gcb.16419
|View full text |Cite
|
Sign up to set email alerts
|

Forest structure and composition alleviate human thermal stress

Abstract: Current climate change aggravates human health hazards posed by heat stress. Forests can locally mitigate this by acting as strong thermal buffers, yet potential mediation by forest ecological characteristics remains underexplored. We report over 14 months of hourly microclimate data from 131 forest plots across four European countries and compare these to open-field controls using physiologically equivalent temperature (PET) to reflect human thermal perception. Forests slightly tempered cold extremes, but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 102 publications
1
27
0
Order By: Relevance
“…1), tree diversity-enhanced temperature buffering may impact forest biodiversity under global warming by reducing the thermophilization of below-canopy communities 7,15,16 . Finally, forest temperature buffering also alleviates heat stress for humans, and our findings indicate that tree species richness may amplify this effect far stronger than previously reported 32 .…”
Section: Discussion and Outlooksupporting
confidence: 55%
See 1 more Smart Citation
“…1), tree diversity-enhanced temperature buffering may impact forest biodiversity under global warming by reducing the thermophilization of below-canopy communities 7,15,16 . Finally, forest temperature buffering also alleviates heat stress for humans, and our findings indicate that tree species richness may amplify this effect far stronger than previously reported 32 .…”
Section: Discussion and Outlooksupporting
confidence: 55%
“…There is ample evidence that forests buffer temperature extremes 2,3,9 and that species identities matter for temperature buffering 4,25 , but the role of tree diversity has largely remained hidden. The few former studies on the role of tree species composition for temperature buffering reported predominantly non-significant effects of species richness 25,32,34 . Positive effects were rare and only found for specific mixtures 4 .…”
Section: Discussion and Outlookmentioning
confidence: 96%
“…functioning. A few recent studies have shown that plants can buffer air temperature inside forests [12][13][14][15] . However, whether plants can contribute to buffering soil temperature is still unclear.…”
mentioning
confidence: 99%
“…Thus, mitigating the effects of extreme weather events on soil temperature fluctuations can contribute to stable ecosystem functioning. A few recent studies have shown that plants can buffer air temperature inside forests 1215 . However, whether plants can contribute to buffering soil temperature is still unclear.…”
mentioning
confidence: 99%
“…Fortunately, we know that heat stress can be buffered, in part, by vegetation in cities 24 . Urban green spaces, and especially urban forests, have proven an effective means through which to ameliorate heat stress through shading and transpirational cooling [25][26][27] . The buffering effect of urban green space is influenced by its area relative to the area of the city and its spatial configuration 28,29 .…”
mentioning
confidence: 99%